Central nervous system neuroplasticity and the sensitization of hypertension. Issue 12 (December 2018) - Johnson, Alan; Xue, Baojian
Abstract The causes of essential hypertension remain an enigma. Interactions between genetic and external factors are generally recognized to act as aetiological mechanisms that trigger the pathogenesis of high blood pressure. However, the questions of which genes and factors are involved, and when and where such interactions occur, remain unresolved. Emerging evidence indicates that the hypertensive response to pressor stimuli, like many other physiological and behavioural adaptations, can become sensitized to particular stimuli. Studies in animal models show that, similarly to other response systems controlled by the brain, hypertensive response sensitization (HTRS) is mediated by neuroplasticity. The brain circuitry involved in HTRS controls the sympathetic nervous system. This Review outlines evidence supporting the phenomenon of HTRS and describes the range of physiological and psychosocial stressors that can produce a sensitized hypertensive state. Also discussed are the cellular and molecular changes in the brain neural network controlling sympathetic tone involved in long-term storage of information relating to stressors, which could serve to maintain a sensitized state. Finally, this Review concludes with a discussion of why a sensitized hypertensive response might previously have been beneficial and increased biological fitness under some environmental conditions and why today it has become a health-related liability. Here, Johnson and Xue describe various physiological and psychosocial challenges that lead to the sensitization of hypertension. These challenges drive neuroplasticity in the brain network controlling sympathetic tone and blood pressure, and provide a new paradigm for understanding essential hypertension. Key points The aetiology of essential hypertension is still unknown. Emerging evidence has shown that the hypertensive response can undergo sensitization. Hypertensive response sensitization (HTRS) involves neuroplasticity induced by a wide range of physiological and behavioural challenges (stressors) occurring throughout life. The cellular and molecular changes that mediate HTRS are located and maintained in the central neural network that controls sympathetic nervous system activity. The neuroplasticity of the sympathetic nervous system provides adaptive blood pressure control, such that an increased hypertensive response (to physiological or psychosocial stressors) is learned and subsequently remembered. Recognition of HTRS and the centrally mediated mechanisms driving the sensitized state provides a new paradigm for understanding essential hypertension and developing new strategies for its prevention and treatment.